Sustainable biofuels from first three alcohol families : A critical review - Muhamad Norkhizan, Abdullah; Ahmad Fitri, Yusop; Rizalman, Mamat; Mohd Adnin, Hamidi; Sudhakar, Kumarasamy; Yusaf, Talal (MDPI, 2023)
With its unique qualities, such as infinite supply, high octane number, and capacity to cut greenhouse gas emissions, alcohol is a viable alternative fuel for SI engines. This review article aims to reveal to readers the effects of alcohol on the performance, combustion behavior, and emission characteristics of SI engines by collecting the outcomes from previous research. This article looks at methanol, ethanol, and butanol fuel qualities. The performance of SI engines with butanol, ethanol, and methanol combined with gasoline is investigated in terms of brake torque, brake power, fuel consumption, thermal efficiency, volumetric efficiency, mean effective pressure, and coefficient of variation under various conditions. Second, in-cylinder pressure, mass fraction burnt, ignition delay, pressure increases, and heat release rates are also used to evaluate the combustion characteristic. Finally, the article discusses pollutant emissions such as CO, CO2, NOx, UHC, and exhaust gas temperature. Methanol, ethanol, and butanol mixed with gasoline increased fuel consumption and lowered spark-ignition engines’ thermal efficiency. When alcohol was combined with gasoline, most research found that CO, NOx, and UHC emissions were reduced due to improved combustion.